Brain activity measured by functional brain imaging predicts breathlessness improvement during pulmonary rehabilitation - Finnegan, SL; Browning, M; Duff, E; Harmer, CJ; Reinecke, A; Rahman, NM; Pattinson, KTS (BMJ Publishing Group, 2022)
Background Chronic breathlessness in chronic obstructive pulmonary disease (COPD) is effectively treated with pulmonary rehabilitation. However, baseline patient characteristics predicting improvements in breathlessness are unknown. This knowledge may provide better understanding of the mechanisms engaged in treating breathlessness and help to individualise therapy. Increasing evidence supports the role of expectation (ie, placebo and nocebo effects) in breathlessness perception. In this study, we tested functional brain imaging markers of breathlessness expectation as predictors of therapeutic response to pulmonary rehabilitation, and asked whether D-cycloserine, a brain-active drug known to influence expectation mechanisms, modulated any predictive model.